2009
DOI: 10.1136/oem.2009.047969
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene-induced neurobehavioral function and neurotransmitter alterations in coke oven workers

Abstract: Occupational B[a]P exposure may reduce coke oven workers' neurobehavioral function and monoamine, amino acid and choline neurotransmitter levels. Moreover, Ach and AchE correlated with neurobehavioral function; AchE has poor specificity, but Ach is a potential biomarker of B[a]P neurotoxicity in coke oven workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 14 publications
3
39
0
Order By: Relevance
“…Our findings of neurobehavioral dysfunction and high 1-OHP level in coke oven workers are consistent with previous investigations [Niu et al, 2010].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings of neurobehavioral dysfunction and high 1-OHP level in coke oven workers are consistent with previous investigations [Niu et al, 2010].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there has been only one report of a lack of association between prenatal exposure to BaP and a measure of neurodevelopment in children [105]. Only one published study has examined BaP neurotoxicity in adults [111]. It described impaired learning and memory in workers exposed up to 1623 ng BaP/m 3 , which is consistent with similar effects in rodents measured by the Morris water maze test.…”
Section: Epidemiological Studies and A Proposed Neurotoxic Moa In Humansmentioning
confidence: 82%
“…YES: Multiple reports of AHR binding to and activation by BaP; activation of AhR (its increased gene expression) was noted in the hippocampus of in utero exposed rat pups [32,85] YES: BaP binds to human AHR to activate AHR-dependent gene expression [122] NO/Maybe: AHR targets CYP1A1 and CYP1B1 were induced in mouse, but not human neuronal progenitor cells, challenged with AhR ligand 3-methylcholanthrene [105][106][107]111] exposure to BaP in rodents leads to altered Nr1, Nr2a, and Nr2b expression in the hippocampus, accompanied by impaired learning and memory [52,[75][76][77][78] or reduction of ''anxietyrelated'' behaviour [74]. Potential inconsistency exists regarding the direction of change of NMADARs' gene expression, as discussed in Section 3.4 above.…”
Section: Key Eventmentioning
confidence: 99%
“…Meanwhile, several studies have reported robust neurotoxic effects as evidenced by deficits in LM mechanisms subsequent to prenatal or subacute B(a)P exposure (Grova et al, 2007;Wormley et al, 2004a). Recently, studies have also suggested that neurotransmitters and morphological changes in neuronal cells played an important role in modulating the neurobehavioral effects of B(a)P (Zhang et al, 2008;Niu et al, 2010). Overall, these results from previous studies suggested that plasticity and behavioral deficits produced as a result of B(a)P exposure are at least, in part, a result of down or up-regulation of gene or protein expression.…”
Section: Introductionmentioning
confidence: 88%